Developement of 3D virtual environment for Teratai College, UiTM Shah Alam using open source platform / Tengku Mohd Najib Tengku Ishak - Tengku Ishak, Tengku Mohd Najib (2006)
Nowadays advances in computer graphics hardware algorithms, visualization and interactive techniques offer the components for high integrated and efficient real-time 3D Virtual Environment. Users having difficulty to imagine how the Teratai College looks like. Therefore a project for developing a web map that enables a user to connect in a virtual visit to Teratai College in UiTM Shah Alam is proposed. Another objective is to implement the virtual environment visit using open source platform which perhaps may generates more 3D project using open source platform. By applying the virtual tools and waterfall model approach methodology, necessary objects would be designed and rendered by. Once built, a user is able to move freely through the building interactively when the 3D objects save as *wrl format can be access by using plug-in player in web format. VRML (Virtual Reality Modelling Language) has been employed to enable virtual reality application to be unplemented on the web as the web maps into 3D environment. The employment of VRML in this context has shown its ability in helping users to meet specific requirement. User now may enjoy the virtual visit and experience by themselves the picture of Teratai College UiTM Shah Alam.